Genetic characterization and molecular epidemiological analysis of novel enterovirus EV-B80 in China - Han, Zhenzhi; Zhang, Yong; Huang, Keqiang; Cui, Hui; Hong, Mei; Tang, Haishu; Song, Yang; Yang, Qian; Zhu, Shuangli; Yan, Dongmei; Xu, Wenbo (Emerging microbes & infections, 2018)
Enterovirus B80 (EV-B80) is a newly identified serotype belonging to the enterovirus B species. To date, only two full-length genomic sequences of EV-B80 are available in GenBank, and few studies on EV-B80 have been conducted in China or worldwide. More information and research on EV-B80 is needed to assess its genetic characteristics, phylogenetic relationships, and association with enteroviral diseases. In this study, we report the phylogenetic characteristics of three Xinjiang EV-B80 strains and one Tibet EV-B80 strain in China. The full-length genomic sequences of four strains show 78.8-79% nucleotide identity and 94-94.2% amino acid identity with the prototype of EV-B80, indicating a tendency for evolution. Based on a maximum likelihood phylogenetic tree based on the entire VP1 region, three genotypes (A-C) were defined, revealing the possible origin of EV-B80 strains in the mainland of China. Recombination analysis revealed intraspecies recombinations in all four EV-B80 strains in nonstructural regions along with two recombination patterns. Due to the geographic factor, the coevolution of EV-B strains formed two different patterns of circulation. An antibody seroprevalence study against EV-B80 in two Xinjiang prefectures also showed that EV-B80 strains were widely prevalent in Xinjiang, China, compared to other studies on EV-B106 and EV-B89. All four EV-B80 strains are not temperature sensitive, showing a higher transmissibility in the population. In summary, this study reports the full-length genomic sequences of EV-B80 and provides valuable information on global EV-B80 molecular epidemiology.